Association between visualization of the perivascular space and morphological changes in the brain among the community-dwelling elderly. Issue 162 (May 2023) - Sugai, Yasuhiro; Niino, Kazuho; Shibata, Akiko; Hiraka, Toshitada; Kobayashi, Atsunori; Suzuki, Keisuke; Iseki, Chifumi; Ohta, Yasuyuki; Kanoto, Masafumi
Abstract: Purpose: We aimed to investigate the association between perivascular space (PVS) visible on MRI and brain atrophy or morphological change using quantitative indexes. Method: This population-based cohort study included 216 older participants. The PVS in basal ganglia (BG-PVS) and cerebral white matter (WM-PVS) was evaluated using a four-point visual rating scale. We segmented brain parenchyma and CSF, and calculated the CSF/intracranial volume ratio, which represents atrophic change. WM lesions were classified using the Fazekas scale. We introduced a new category "idiopathic normal pressure hydrocephalus (iNPH)-like conformation", which was based on two quantitative indexes: Evans index and callosal angle. The association between PVS grade and demographic or morphological factors was evaluated. Results: A stepwise increase in the CSF/intracranial volume ratio with BG-PVS grade progression and a stepwise decrease with WM-PVS grade progression were observed. A higher CSF/intracranial volume ratio was significantly related to a higher BG-PVS grade in a univariate analysis, but this significance disappeared in a multivariate analysis. The iNPH-like group was significantly related to a lower WM-PVS grade in a univariate analysis, and this significance remained in a multivariate analysis. Conclusions: The association between BG-PVS enlargement and atrophic changes was verified. On the contrary, WM-PVS showed a different trend, and a lower WM-PVS grade was associated with an iNPH-like conformation. This result implies that the less-visible WM-PVS on imaging as well as BG-PVS enlargement would reflect abnormal brain change.